Prarancangan Pabrik Ferrosulfate Heptahydrate dari Pickling Liquor dan Asam Sulfat Kapasitas 25.000 Ton/Tahun - Rahayu, Esti, Emi Erawati, S.T., M.Eng, Kusmiyati, S.T., M.T., Ph.D (2017)
Ferrosulfate Heptahydrate is a product commonly used in the textile industry, pharmaceutical and ink makers. To meet domestic needs and their export opportunities are still open, the plant is designed ferrosulfate heptahydrate with a capacity of 25,000 tons / year of raw materials picling liquor and sulfuric acid. The factory is planned to stand in Gresik, East Java in 2020. The process of making ferrosulfate heptahydrate reaction performed on Flow stirred tank reactor (RATB) at 85oC operating conditions at a pressure of 1 atm. Endothermic reaction takes place in non-adiabatic. After the manufacturing process and then do the process of crystal formation takes place in kristaliser 40oC operating conditions. Then continue the process of purification by means of separation of crystals with mother liquornya. Raw material requirements to meet the target of the resulting product is a pickling liquor as much 7,024.31 kg / h and sulfuric acid as 21,306.51 kg / hour. Utility requirements in each year in the form of process water needs as much 17,581.20 kg / h, for cooling water as much as 3,864.95 kg / hr, steam providers as much 6,981.55kg / hr, 244.89 kW much electricity, and fuel as much as 0.16 m3 / h. The establishment of the plant would also have to consider the number of workers. Ferrosulfate Heptahydrate factory will be established with a number of employees 191 people. The shape of the selected company is a Limited Liability Company (PT). Systems based on the division of employees working hours of employees shift and non-shift, amounting to 193 people. Ferrosulfate heptahydrate factory is at low risk with a fixed capital of Rp 484,958,484,483.23 and working capital of Rp 371,980,309,222.73. Profit before tax of Rp 277.665.288,932.30 per year and after taxes amounting to Rp 194,365,702,252.61 per year. From the calculations, the value of the Return On Investment (ROI) before tax after tax 57.26% and 40.08%. Pay Out Time (POT) before tax is 1.49 years and 2.00 years after tax. Break Even Point (BEP) amounted to 44.00% and Shut Down Point (SDP) of 32.32%. Based on the calculation of technical and economic evaluation that done, then the ferrosulfate heptahydrate plant with a capacity of 25,000 tons per year feasible to set up.